Analisis Pengaturan Jarak Cahaya Lampu Halogen Pada Rancang Bangun Solar Test Simulator - ., Cholish; Faza, Sharfina; Hajar, Ibnu; ., zumhari; Azis, Abdul; ., abdullah (Rekayasa Material, Manufaktur dan Energi, 2023)
This study focuses on the use of halogen lamps in the design of a Solar Test Simulator to simulate sunlight conditions in testing solar panels. Halogen lamps are chosen as the light source due to their ability to approximate the solar spectrum, enabling testing of solar cells in a controlled laboratory environment. However, precise adjustment of halogen lamp light is crucial to ensure the accuracy and consistency of test results. The design of the Solar Test Simulator for Solar Panels involves configuring the placement of solar panels so that the designed tool can provide simulation based on actual solar panel measurements. The performance of solar panels is displayed through a monitor placed in the design, providing comprehensive information about the solar panels. Limitations in the placement of solar panels do not provide reference regarding measurement conditions based on the angle of incoming sunlight. Therefore, further design is needed concerning the positioning of solar panels during measurements. The development in this tool's design includes adjustments to the height of the halogen lamp from the solar panel, specifically at heights of 0.328m, 0.366m, and 0.405m.